Combination of Xpert MTB/RIF and TBAg/PHA Ratio for Prompt Diagnosis of Active Tuberculosis: A Two-Center Prospective Cohort Study - Wang, Feng; Liu, Kui; Peng, Jing; Luo, Ying; Tang, Guoxing; Lin, Qun; Hou, Hongyan; Liu, Weiyong; Wang, Jing; Fang, Zemin; Kuang, Haobin; Sun, Ziyong (Frontiers in Medicine, 2020)
The prompt diagnosis of active tuberculosis (ATB) is still a challenge in clinical practice, especially in TB-endemic countries. We prospectively enrolled consecutive patients with suspected pulmonary TB from two tertiary hospitals. Acid-fast staining (AFS), Xpert MTB/RIF (Xpert), Mycobacterium tuberculosis culture, and T-SPOT.TB were simultaneously performed. For diagnosis of ATB in Tongji Hospital, the sensitivity of AFS was low (17.70%). The sensitivity of Xpert and culture were moderate (53.54% and 46.46%). The sensitivity of T-SPOT.TB was relatively high (81.42%), but the specificity was limited (71.55%). Calculation of the ratio of TB-specific antigen to phytohaemagglutinin (TBAg/PHA) of T-SPOT.TB assay increased the specificity (95.98%) but with a loss of sensitivity (62.83%).Combination of Xpert and culture slightly increased the sensitivity compared to using these methods separately. Combination of Xpert and TBAg/PHA ratio increased both sensitivity and specificity. When the cutoff value of TBAg/PHA ratio was 0.2, the sensitivity and specificity of combination of Xpert and TBAg/PHA ratio were 85.84% and 95.98%, respectively. The performance of combination of Xpert and TBAg/PHA ratio was similar in Guangzhou Chest Hospital. Our data suggest that combination of Xpert and TBAg/PHA ratio may be a good algorithm for prompt diagnosis of ATB in high endemic areas.